The Evolution of Flavonoid Biosynthesis: A Bryophyte Perspective - Davies, Kevin M.; Jibran, Rubina; Zhou, Yanfei; Albert, Nick W.; Brummell, David A.; Jordan, Brian R.; Bowman, John L.; Schwinn, Kathy E. (Frontiers in Plant Science, 2020)
The flavonoid pathway is one of the best characterised specialised metabolite pathways of plants. In angiosperms, the flavonoids have varied roles in assisting with tolerance to abiotic stress and are also key for signalling to pollinators and seed dispersal agents. The pathway is thought to be specific to land plants and to have arisen during the period of land colonisation around 550-470 million years ago. In this review we consider current knowledge of the flavonoid pathway in the bryophytes, consisting of the liverworts, hornworts and mosses. The pathway is less characterised for bryophytes than angiosperms, and the first genetic and molecular studies on bryophytes are finding both commonalities and significant differences in flavonoid biosynthesis and pathway regulation between angiosperms and bryophytes. This includes biosynthetic pathway branches specific to each plant group and the apparent complete absence of flavonoids from the hornworts.